Implementation of Goods and Services Procurement through E-Purchasing at the Ujung Menteng Urban Village Office Working Unit - Widianingsih, Novita; Arnita, Vina (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2023)
With the enactment of the e-purchasing system in the expenditure of goods and services by the Government Institutions Province of Special Region of Jakarta, a few e-purchasing users are still confused on how-to-use the application, particularly at the Urban Village of Ujung Menteng Working Unit. One of the causes is a lack of training and guidance information on using the application. The purpose of this research is to inform the readers on how the system and procedures in realizing expenditure on goods and services through e-purchasing application. The method used in this research is qualitative descriptive. The result of this research is that the implementation of the e-purchasing application at the Ujung Menteng Village Office Working Unit is running well. Thus, the expense of goods and services in the running year becomes more effective and efficient under expectations.